A network meta-analysis of psychosocial interventions for refugees and asylum seekers with PTSD - Pim Cuijpers; Marianna Purgato; Michela Nosè; Giovanni Ostuzzi; Marit Sijbrandij; Federico Tedeschi; Giulia Turrini; Corrado Barbui; Cinzia Del Giovane; Nexhmedin Morina; Ahlke Kip; Wietse Tol; et al. (BMJ Global Health)
Introduction Refugees and asylum seekers are vulnerable to common mental disorders, including post-traumatic stress disorder (PTSD). Using a network meta-analysis (NMA) approach, the present systematic review compared and ranked psychosocial interventions for the treatment of PTSD in adult refugees and asylum seekers.Methods Randomised studies of psychosocial interventions for adult refugees and asylum seekers with PTSD were systematically identified. PTSD symptoms at postintervention was the primary outcome. Standardised mean differences (SMDs) and ORs were pooled using pairwise and NMA. Study quality was assessed with the Cochrane Risk of Bias (RoB) tool, and certainty of evidence was assessed through the Confidence in Network Meta-Analysis application.Results A total of 23 studies with 2308 participants were included. Sixteen studies were conducted in high-income countries, and seven in low-income or middle-income countries. Most studies were at low risk of bias according to the Cochrane RoB tool. NMA on PTSD symptoms showed that cognitive behavioural therapy (CBT) (SMD=−1.41; 95% CI −2.43 to −0.38) and eye movement desensitisation and reprocessing (EMDR) (SMD=−1.30; 95% CI −2.40 to −0.20) were significantly more effective than waitlist (WL). CBT was also associated with a higher decrease in PTSD symptoms than treatment as usual (TAU) (SMD −1.51; 95% CI −2.67 to −0.36). For all other interventions, the difference with WL and TAU was not significant. CBT and EMDR ranked best according to the mean surface under the cumulative ranking. Regarding acceptability, no intervention had less dropouts than inactive interventions.Conclusion CBT and EMDR appeared to have the greatest effects in reducing PTSD symptoms in asylum seekers and refugees. This evidence should be considered in guidelines and implementation packages to facilitate dissemination and uptake in refugee settings.